Pendampingan Pengurusan Sertifikasi Tanah Wakaf Sebagai Wujud Perlindungan dan Kepastian Hukum Atas Tanah Wakaf di Masjid Baitul Muttaqin Nglaban Babadan Patianrowo Nganjuk - M. Burhanuddin Ubaidillah; M. Barid Nizaruddin Wajdi; Juni Iswanto (LP3M STAI Darussalam Krempyang Nganjuk, 2021)
Waqf land certificate is one proof of the transfer of rights between waqf and nazhir. The position of the waqf land certificate provides legal certainty and legal protection for the land that has been waqf. The implication of not having waqf land certification, or Waqf Pledge Deed (AIW) or Deed in lieu of Waqf Pledge Deed (APAIW) which explains the occurrence of waqf legal events will experience difficulties in the evidentiary process when a dispute occurs. The registration and recording of waqf land to the National Land Agency (BPN) provides legal certainty and legal protection by the state for waqf land by issuing proof of waqf land certificates. Land that has been waqf by the waqf has a clear legal status in accordance with positive law in force in Indonesia, also in accordance with QS. al-Baqarah (2) paragraph 282. This article is focused on counseling and assisting waqf land certification, in the form of a plot of productive rice fields from Mrs. Hj. Siti Khodijah who is in the Sawahan Lengkong area to Ta'mir and Nadzir Baitul Muttaqin Mosque Nglaban Babadan Patianrowo Nganjuk in order to provide protection and legal certainty for waqf land.